Education for Energy Efficiency through an Educational Game - Mesquita, Leonardo [UNESP]; Monteiro, Marco Aurelio A. [UNESP]; Sena, Galeno J. de [UNESP]; Ninomiya, Mauricio P. [UNESP]; Costa, Charles A. da [UNESP] (Ieee, 2013)
This paper presents an assessment of an educational game for teaching the efficient use of electricity. Developed with Adobe Flash (R), it is a virtual board game where participants choose a car that starts the path and reaches the same final goal, going through a number of track steps defined in terms of a dice that each player rolls in turn. The car moves if the participant is able to correctly answer a question that is randomly generated by the software. The objective of the game is to answer questions related to energy efficiency promoting a healthy and attractive learning process for participants on concepts related to energy efficiency such as: the rational use of energy, the basic concepts of forms of energy generation, among others. The main objective of this paper is to assess the impact of the application of this virtual game in the teaching and learning process of high school students. Therefore, the game was applied in the discipline of physics in a class of junior high public school in the state of Sao Paulo. Initially, the class that had 43 students was divided into 10 groups of 4 students, and 1 group of 3 students. Each student group competed with one another. The idea was that each of them should indicate a student who was the representative of this group until only 4 group leaders were selected for the finals. At this stage, each student could interact with a group of up to ten students that acted as advisers. The adopted assessment process is based on the model proposed by Savi [7]. Then, at the end of the game, the students answered a prepared questionnaire based on the model proposed by Savi. According to Savi, although there are significant studies that show the importance of educational games for the process of cognitive development and learning concepts of students, there are few papers that present forms of assessing the potential of these resources. Thus, the assessment criteria proposed by Savi are based on the model of training evaluation by Kirkpatrick [3], taken as a reference to measure the efficiency of processes of continuing education courses for professionals. The authors assert that the metric of the evaluation proposed to assess the game is based on the first level of the model proposed by Kirkpatrick.
Keywords: educational game; game-based learning; education; energy efficiency